Prolonged Course of COVID-19-Associated Pneumonia in a B-Cell Depleted Patient After Rituximab - Kos, Igor; Balensiefer, Benedikt; Roth, Sophie; Ahlgrimm, Manfred; Sester, Martina; Schmidt, Tina; Thurner, Lorenz; Bewarder, Moritz; Bals, Robert; Lammert, Frank; Stilgenbauer, Stephan; Kaddu-Mulindwa, Dominic (Frontiers in Oncology, 2020)
Patients with pre-existing comorbidities and immunosuppression are at greater risk for SARS-CoV-2 infection and severe manifestations of COVID-19. This also includes cancer patients, who are shown to have a poor prognosis after infection. Here, we describe the case of a 72-year old male patient with B-cell depletion after maintenance treatment with rituximab for non-Hodgkin-lymphoma who had a prolonged COVID-19 course and initial false negative test results. Our case highlights the diagnostic pitfalls in diagnosing COVID-19 in B-cell depleted patients and discuss the role of B-cell depletetion in the course and treatment of COVID-19. Furthermore, we investigated peripheral blood monocytes and SARS-CoV-2 specific T cells in our patient. In conlcusion, our case report can help physicians to avoid diagnostic pitfalls for COVID-19 in hemato-oncological patients under chemotimmunotherapy and tries to explain the role of B-cell depletion and SARS-CoV-2 specific T cells in this context.